Challenges in Evaluating Safety and Efficacy in Drug Development for Rare Diseases: A Review for Pharmacists. (June 2021) - Shah, Kanya K.; Kogut, Stephen; Slitt, Angela
A rare disease, or orphan disease, in the United States is a condition with a national prevalence of fewer than 200, 000 diagnoses. As therapies for rare diseases are developed and brought to market, pharmacists should understand the challenges of drug development for rare diseases and aid in educating patients about the approval process for rare disease therapies. Developing drugs for treating rare diseases presents unique challenges in proving the drug's safety and efficacy with adequate study design, power, and validity. Results of the clinical trials for rare diseases may be weakened by small patient populations, limited disease information, and difficulty defining end points and biomarkers. In addition to investigational barriers, pharmaceutical companies face financial barriers in justifying the investment of bringing a rare disease therapy to market. Federal programs, such as the Orphan Drug Act of 1983, expedited review, the Rare Pediatric Disease Priority Review Vouchers (RPD PRV) program, and the 21st Century Cures Act, give pharmaceutical companies motivation to develop therapies for rare diseases. The objective of this article is to provide pharmacists with an understanding of the challenges in designing clinical trials for drugs for rare diseases and discuss federal programs that address efforts to develop safe and efficacious drugs for rare diseases.